The Malaysian Moon Moth (Actias maenas): Ecological Significance, Sericogenic Potential, and Conservation Challenges (Bhartiya Knowledge Systems, 2025)
The Actias maenas moth, commonly known as the Malaysian Moon Moth, has been recognized for over a century and is highly sought after by collectors; however, the larval stages of this species remain poorly documented. It extends from the sub-Himalayan areas of northeastern India across the majority of mainland Southeast Asia and the Greater Sunda Islands, covering more than 4000 km. In India, five species have been reported so far: Actias maenas (Malaysian Moon Moth), Actias selene (Indian Moon Moth), Actias rhodopneuma (Asian Moon Moth), Actias parasinensis (Western Chinese Moon Moth), and Actias keralana (Kerala Moon Moth) (Sondhi et al., 2025). The Malaysian Moon Moth is notable for its graceful appearance and intricate patterns, making it one of the most beautiful moths and a favorite among nature enthusiasts.